Amplitude of Low-Frequency Fluctuation to Determine Disturbed Spontaneous Brain-Activity Pattern in Patients with Diabetic Optic Neuropathy - Wang XY; Xu SH; Wei H; Kang M; Zou J; Ling Q; Huang H; Chen X; Wang YX; Shao Y; Yu Y (Diabetes, Metabolic Syndrome and Obesity, 2023)
Xiao-Yu Wang,1– 3,* San-Hua Xu,3,* Hong Wei,3,* Min Kang,3 Jie Zou,3 Qian Ling,3 Hui Huang,3 Xu Chen,4 Yi-Xin Wang,5 Yi Shao,3 Yao Yu1 1Department of Endocrinology and Metabolism, The First Affiliated Hospital of Nanchang University, Jiangxi Clinical Research Center for Endocrine and Metabolic Disease, Jiangxi Branch of National Clinical Research Center for Metabolic Disease, Nanchang, Jiangxi, 330006, People’s Republic of China; 2The First Clinical Medical College, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China; 3Department of Ophthalmology, The First Affiliated Hospital of Nanchang University, Jiangxi Branch of National Clinical Research Center for Ocular Disease, Nanchang, Jiangxi, 330006, People’s Republic of China; 4Department of Ophthalmology and Visual Sciences, Maastricht University, Maastricht, Limburg Province, 6200MA, Netherlands; 5School of Optometry and Vision Sciences, Cardiff University, Cardiff, CF244HQ, UK*These authors contributed equally to this workCorrespondence: Yi Shao, Department of Ophthalmology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China, Email freebee99@163.com Yao Yu, Department of Endocrinology and Metabolism, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China, Email yuyao1234562023@163.comPurpose: This study aimed to explore the spontaneous brain activity in patients with diabetic optic neuropathy (DON) by using the amplitude of low-frequency fluctuation (ALFF) technique.Methods: Sixteen DON patients and 16 age- and sex-matched healthy controls (HCs) were recruited. ALFF along with functional MRI method was used to detect the intrinsic brain activity alterations. The mean values of ALFF in DON patients and HCs were analyzed by receiver operating characteristic (ROC) curves. Pearson’s correlation analysis was used to determine the correlation between Hospital Anxiety and Depression Scale (HADS) and ALFF values of DONs.Results: The DON group showed significantly increased ALFF values in the fusiform gyrus, and decreased ALFF values in the medial frontal gyrus/left frontal superior orbit/right frontal medial orbit, and left frontal inferior triangle. ROC curve analysis indicated that the accuracy of AUC was good. The anxiety scale and depression scale of the DON group were negatively correlated with the ALFF values of the medial frontal gyrus.Conclusion: DON is a neurodegenerative disease involving multiple brain regions. The abnormal activity of neurons in these brain regions helps to reveal the underlying neural mechanisms of brain activity related to DON.Keywords: ALFF, fMRI, diabetic optic neuropathy, spontaneous brain activity